Bipolar Disorder due to Subdural Hematoma Case Report - Kılıç, Serbülent; Sezer, Fatih; Cantürk, Gürol (The Bulletin of Legal Medicine, 2017)
A court in Ankara asked for a report from our department of forensic medicine about an injury case due to a traffic accident. The report should include the disability rate and the duration of no functionality. The history and physical examination of the case revealed the diagnosis of bipolar disorder due to subdural hematoma in right parietotemporal region of head. Bipolar disorder is a relapsing disease with manic and depressive periods that exists in group of mood disorders. The etiology of Bipolar disorder is still unknown, though genetics, structural or biochemical abnormalities of the brain, endocrinal disorders, neurotransmitters, and trauma are among the probable causes of the disease. A case of bipolar disorder subsequent to a subdural hematoma in right parietotemporal region due to traffic accident is rarely met. Head traumas can cause psychopathologic disorders. Our aim to present the current case was to suggest that psychopathological disorders can rarely occur, and that forensic medicine specialists should keep this probability in mind.